Biofungicide Bacillus subtilis Ch-13 in the control of Hypomyces perniciosus (wet bubble disease) in industrial-scale mushroom cultivation - Potočnik, Ivana; Milijašević-Marčić, Svetlana; Šantrić, Ljiljana; Luković, Jelena; Todorović, Biljana; Rekanović, Emil (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2026)
The current study aimed to evaluate the efficacy of the biofungicide Bacillus subtilis Ch-13 in the suppression of natural infection of white button mushrooms (Agaricus bisporus) with Hypomyces perniciosus (causal agent of wet bubble disease), as well as its impact on mushroom yield in industrial-scale cultivation. The biofungicide B. subtilis Ch-13 was applied at a total concentration of 60 ml per m2 of casing layer in two different procedures — using either three (30 + 2 × 15 ml m-2) or two split doses (2 × 30 ml m-2) — and then its effects were compared to those of the fungicide prochloraz applied at a standard application rate. The efficacy of the biofungicide was significantly higher when applied in three split doses (29.7%), than in two (15.7%). Though the efficacy of B. subtilis Ch-13 (≈30%) against H. perniciosus was low in comparison to that of prochloraz (≈68%), B. subtilis Ch-13 slightly reduced wet bubble symptoms. Furthermore, the highest increase in mushroom yield was achieved when B. subtilis Ch-13 was applied in three split doses (14%), rather than two (2%), compared to the untreated control. In comparison to prochloraz, three and two split applications of B. subtilis Ch-13 enhanced mushroom yield by up to 17% and 4%, respectively. Regarding its efficacy in wet bubble disease control and augmentation of mushroom yield, B. subtilis Ch-13 was much more effective when applied in three split doses, than in two. Therefore, this study supports the application B. subtilis Ch-13 in three split doses (30 + 2 × 15 ml m-2, on the second day and two weeks after casing, and after the first fruiting flush, respectively) to suppress H. perniciosus and increase mushroom yield.
Keywords: edible mushrooms; biocontrol agent; disease control